Comparative assessment of the strength and endurance of the respiratory muscles in skiers and wrestlers - Segizbaeva, M. O. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to compare the maximal inspiratory strength and endurance of inspiratory muscles in athletes engaged in different types wrestling and skiing.